Respuesta :
Answer:
The quadratic equation is [tex]\displaystyle\bf y=-\frac{17}{25} x^2-\frac{102}{25} x-\frac{3}{25}[/tex].
Step-by-step explanation:
To find the quadratic equation that has a vertex at (-3, 6) and passes through the point (2, -11), we assume that the quadratic equation is:
[tex]\boxed{y=ax^2+bx+c}[/tex]
Given:
- vertex at (-3, 6) which means:
(i) the axis of symmetry is x = -3
(ii) the function passes through the point (-3, 6)
- the function passes through the point (2, -11)
Using these informations, we can create a system of equation:
(1) axis of symmetry is x = -3
The formula of axis of symmetry: [tex]\boxed{x=-\frac{b}{2a} }[/tex]
[tex]\displaystyle -\frac{b}{2a} =-3[/tex]
[tex]b=6a\ ...\ [1][/tex]
(2) passes through the point (-3, 6)
[tex]y=ax^2+bx+c[/tex]
[tex]6=a(-3)^2+b(-3)+c[/tex]
[tex]9a-3b+c=6\ ...\ [2][/tex]
(3) passes through the point (2, 11)
[tex]y=ax^2+bx+c[/tex]
[tex]11=a(2)^2+b(2)+c[/tex]
[tex]4a+2b+c=-11\ ...\ [3][/tex]
Substituting [1] into [2]:
[tex]9a-3b+c=6[/tex]
[tex]9a-3(6a)+c=6[/tex]
[tex]-9a+c=6\ ...\ [4][/tex]
Substituting [1] into [3]:
[tex]4a+2b+c=-11[/tex]
[tex]4a+2(6a)+c=-11[/tex]
[tex]16a+c=-11\ ...\ [5][/tex]
Combining [4] & [5]
[tex]-9a+c=6[/tex]
[tex]16a+c=-11[/tex]
----------------------- (-)
[tex]-25a=17[/tex]
[tex]\displaystyle\bf a=-\frac{17}{25}[/tex]
Substitute the value of a to [1]
[tex]b=6a[/tex]
[tex]\displaystyle b=6\left(-\frac{17}{25} \right)[/tex]
[tex]\bf\displaystyle b=-\frac{102}{25}[/tex]
Substitute the values of a and b to [3]
[tex]4a+2b+c=-11[/tex]
[tex]\displaystyle 4\left(-\frac{17}{25} \right)+2\left(-\frac{102}{25} \right)+c=-11[/tex]
[tex]\displaystyle\bf c=-\frac{3}{25}[/tex]
Therefore, the quadratic equation is [tex]\displaystyle\boxed{y=-\frac{17}{25} x^2-\frac{102}{25} x-\frac{3}{25}}[/tex]